Roots, Routes, and Routers: Communications and Media of Contemporary Social Movements - Lim, Merlyna (Journalism & Communication Monographs, 2018)
This monograph is an interdisciplinary analysis of the complexity of communications and media as they are embedded in the making and development of contemporary social movements, in three parts. The first part, Roots, provides a broad context for analyzing communications and media of contemporary social movements by tracing varied and multifaceted roots of the wave of global protests since 2010. The second part, Routes, maps out the routes that social movements take, trace how communications and media are entangled in these routes, and identify various key mechanisms occurring at various junctures of movements’ life cycles. The last part, Routers, explores roles of human and nonhuman, fixed and mobile, traditional and contemporary, digital and analog, permanent and temporal routers in the making and development of social movements. These analyses of roots, routes, and routers are mutually intertwined in broadening and deepening our understanding of the complexity of communications and media in contemporary social movements.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8xNTIyNjM3OTE4NzcwNDE5